2005
DOI: 10.1063/1.1863459
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of nanocrystalline diamond powders studied by powder diffractometry

Abstract: High resolution x-ray diffraction peaks of diamond nanosize powders of nominal sizes ranging from 5 to 250nm were analyzed and provided information on grain structure, average size of crystallites, and concentration of dislocations. Selected samples were heat treated at 1670K at pressures 2.0 and 5.5GPa or had surface modified by outgassing, heat treatment at vacuum conditions, and by controlled adsorption of gases. The apparent lattice parameter method was applied to characterize the structure of a shell-core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…A previous report indicated that even a weak oxygen concentration can accelerate the graphitization kinetics of detonation NDs and affects the nature of sp 2 ‐induced structures . A similar catalytic effect of oxygen was proposed for graphitization of diamond crystals . Oxygen may promote a new route for diamond conversion into sp 2 forms .…”
Section: Discussionmentioning
confidence: 65%
“…A previous report indicated that even a weak oxygen concentration can accelerate the graphitization kinetics of detonation NDs and affects the nature of sp 2 ‐induced structures . A similar catalytic effect of oxygen was proposed for graphitization of diamond crystals . Oxygen may promote a new route for diamond conversion into sp 2 forms .…”
Section: Discussionmentioning
confidence: 65%
“…Different synthesis atmospheres may also differ in the amount of gases containing reactive oxygen from the atmosphere or desorbing from the precursor. The catalytic effect of oxygen decreases the onset of graphitization and increases the graphitization rate, which may lead to different carbon nanostructures [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was observed for 5 nm grain size diamond powders that the broadening of peak profiles is resulted rather by the small crystallite size and the stacking faults and not by dislocations, see Fig. 17 [112]. Assuming a shell-core model of the diamond nanoparticles, the defect structure of the internal region and the shell strains were obtained from the line broadening and the diffraction vector dependence of the apparent lattice parameter, respectively [112][113][114].…”
Section: Carbon and Diamondmentioning
confidence: 99%